Uji Patogenisitas Bakteri Pasteuria penetrans terhadap Nematoda Puru Akar (Meloidogyne spp.) - Mulyadi Mulyadi; B. Triman; Bambang R. T. P. (Jurnal Perlindungan Tanaman Indonesia, 1996)
The objective of the research was to study the effectiveness of P. penetrans for controlling root-knot nematodes (Meloidogyne spp.) in micro plot and in the field. The pathogenicity study in micro plot was done in Banguntapan, and field experiment was done in Ngipiksari, Pakem, Steman, Yogyakarta. The plots were arranged in Randomized Completely Block Design with three replications. The treatments used in the research were: isolat no. 2 and 3 of P. penetrans; carbofuran nematicide. and control. The results in micro plot test were: 1) root damage caused by root-knot nematodes in plot treated with P. penetrans lower than the control, and 2) percentages of parasitism of P. penetrans were 63.57 % (in isolate no. 2) and 53.46 % (in isolate no. 3). In field experiment the results showed: 1) P. penetrans found to be effective in reducing root damage caused by Meloidogyne spp. especially in 45 days old of tomato plant, whereas in 90 days old the effectiveness were decreased; 2) P. penetrans was able to grow and reproduction in the field: 3) the level of parasitisms of P. penetrans were increased rapidly during the experiment: and 4) the highest yield was found in tomato treated with carbofuran and followed by isolate 2, isolate 3, and control.